The Implementation Of Genre Approach On Students’ Skill In Writing Anecdot Text At SMA Nusa Penida Medan In 2018 – 2019 School Year - Affan Lubis, Salamuddin Selian (CV. PUSDIKRA MITRA JAYA, 2022)
This study was about the effect of two teaching approaches on the students’ writing achievement. The two teaching approaches were Process Approach and genre Approach. An experimental research design was used to conduct the study. The study involved the Grade XI students of SMA Nusa Penida Medan in 2018-2019 School Year the samples were 40 students divided into two experimental groups which were given a pretest. The first group was the first experimental one taught with process approach while the second experimental group was taught with genre approach. After giving the treatment, a post test was administered to both groups to have the data. The data were, then analyzed by using t-test. The findings showed that both approaches significantly affected the students’ achievement in writing anecdote text. It was indicated by the value of the t-observed which was greater than the t-table. However, there was no significant difference of the implementation of both approaches. Based on the result of the study, both approaches were suggested to be used in the language teaching learning process to improve the students’ achievement especially in writing anecdote text.